Regulatory enforcement of minimum wage policy: An examination of street-level bureaucrats’ discretion in Malaysia / Mohammed Salah Hassan - Mohammed Salah , Hassan (2021)
Regulatory enforcement is a multifaceted phenomenon that revolves around the concept of discretion of Street-Level Bureaucrats (SLBs). Discretion can be defined as the ability to freely decide on how to deliver services to the clients/public. Regulations are enforced by the decisions made by bureaucrats when they interact with clients. By combining street-level bureaucracy and responsive regulation theories, this study is set to examine how different factors shape the discretion of street-level bureaucrats. This study is built on available literature pertaining to SLBs and policy implementation to provide a comprehensive understanding of regulation enforcement in Malaysia. SLBs are the Labor Inspectors who are responsible for the enforcement of minimum wage in Malaysia. The study’s main contribution is examining how personal characteristics, internal organizational factors, and a multidimensional enforcement style shape the discretion of bureaucrats in Malaysia. The study’s main finding highlights that Labor Inspectors in Malaysia demonstrate a range of enforcement style dimensions when enforcing the minimum wage. The novelty of this thesis is in highlighting two main constructs; willingness to implement, and client meaningfulness, and their importance in shaping policy implementation and its effect on street-level bureaucrats' behavior, also these constructs are likely contributing to the imperfect enforcement of the minimum wage policy. Furthermore, this study demonstrates that enforcement style consists of three dimensions; legal, facilitation, and accommodation. Finally, the empirical finding of this study highlights that discretion of street-level bureaucrats is influenced by various factors that ultimately define the enforcement process.